Toxocara canis infections in mice: from subtle to severe consequences in 100 weeks - Bernardová, Nicol; Novák, Jan; Fan, Chia-Kwung; Kolářová, Libuše; Chanová, Marta (Journal of helminthology, 2025)
Toxocara canis is a widespread parasite of canids with a wide range of paratenic hosts, but also one of the overlooked agents causing nervous system infections of humans. Previous experimental infections of mice demonstrated the impact of high infection doses of larvae on neurobehavioral disorders and pathological changes. In contrast to previous studies, we aimed to investigate the long-term (up to 100 weeks) impact of low- to high-dose infection in mice. We focused on their physical condition, motor skills, and the accompanying pathologies in the brain. Three groups of BALB/c mice were infected with 10, 100, and 1000 T. canis larvae/mouse and specific anti-T. canis excretory-secretory antigens immunoglobulin G antibody response, general condition, and motor skills were tested in defined intervals within 100 weeks after infection. The number of larvae in selected organs was assessed and the pathological changes in the brain were studied histologically. As a result, subtle to severe impairments in general condition and motor skills were detected, with generally earlier onsets occurring the higher the infection dose was. The specific immunoglobulin G antibody levels corresponding to the infection dose were detected in all infected groups. Necrosis, cellular infiltrations, and foamy cells developed in moderate- and high-infection dose mice, in contrast with hemorrhages detected in all groups. This study demonstrated the long-term negative impact of T. canis infection on the paratenic host, particularly at moderate and high infectious doses. Although pathological changes in the brain were observed even in low-infection dose mice, their physical and motor condition was comparable to the control group.
Keywords: Antibodies, Helminth; Animals; mice; Toxocara canis; toxocarosis; Female; parasite; imunoglobulin G; Toxocariasis; ženské pohlaví; protilátky helmintové; Mice; motor impairment; Mice, Inbred BALB C; mozek; myši; Immunoglobulin G; helminth infection; nematode infection; brain pathology; Male; modely nemocí na zvířatech; Brain; myši inbrední BALB C; toxokaróza; Disease Models, Animal; Larva; zvířata; mužské pohlaví; larva